2002
DOI: 10.4319/lo.2002.47.5.1468
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of food resources for zooplankton (Daphnia) in a tidal freshwater system (Sacramento‐San Joaquin River Delta)

Abstract: We examined the relative nutritional values of natural phytoplankton and particulate detritus for zooplankton growth in a detritus‐rich environment. Seston was collected seasonally from four different habitat types in a tidal freshwater system and fed to juvenile Daphnia magna under controlled culture conditions by use of a flow‐through design. Seston particulate organic carbon (POC) and chlorophyll a contents ranged from ~330 to 3,800 µg L-1 POC and 1.4 to 45 µg L-1 Chl a. A partial residual analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 42 publications
7
92
0
Order By: Relevance
“…Like many other urbanized estuaries around the world, the SFE has experienced perturbations in key ecosystem drivers, including sediment and nutrient loads (Schoellhamer 2011;Jassby 2008), quantity and diversity of toxic pollutants (Brooks et al 2012), decreased phytoplankton biomass, and a loss of diatoms (e.g., Alpine and Cloern 1992;Kimmerer 2004;Dugdale et al 2007), and changes in zooplankton and fish (Mueller-Solger et al 2002;Kimmerer 2005). Although the original authors of the light-utilization model for the SFE (Cole and Cloern 1984) predicted that the empirical efficiency factor y would likely respond to such changes, this parameter has been previously recalculated for the northern estuary only twice (Alpine and Cloern 1992;Jassby et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Like many other urbanized estuaries around the world, the SFE has experienced perturbations in key ecosystem drivers, including sediment and nutrient loads (Schoellhamer 2011;Jassby 2008), quantity and diversity of toxic pollutants (Brooks et al 2012), decreased phytoplankton biomass, and a loss of diatoms (e.g., Alpine and Cloern 1992;Kimmerer 2004;Dugdale et al 2007), and changes in zooplankton and fish (Mueller-Solger et al 2002;Kimmerer 2005). Although the original authors of the light-utilization model for the SFE (Cole and Cloern 1984) predicted that the empirical efficiency factor y would likely respond to such changes, this parameter has been previously recalculated for the northern estuary only twice (Alpine and Cloern 1992;Jassby et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in order for emergent, terrestrial, or floating aquatic vegetation to be incorporated by zooplankton and other suspension feeders, it would have to be routed through a detrital microbial loop. However, experimental work shows that the detrital-derived energy is of minor significance to pelagic pathways compared to phytoplankton, which is far more bioavailable (Sobczak et al 2002(Sobczak et al , 2005 and nutritious for zooplankton (Mueller-Solger et al 2002). This study and others in the estuary have demonstrated, using different approaches, that phytoplankton is the dominant energy source for pelagic consumers (Canuel et al 1995;Jassby and Cloern 2000;Mueller-Solger et al 2002;Sobczak et al 2002Sobczak et al , 2005.…”
Section: Pelagic Food Websmentioning
confidence: 99%
“…However, experimental work shows that the detrital-derived energy is of minor significance to pelagic pathways compared to phytoplankton, which is far more bioavailable (Sobczak et al 2002(Sobczak et al , 2005 and nutritious for zooplankton (Mueller-Solger et al 2002). This study and others in the estuary have demonstrated, using different approaches, that phytoplankton is the dominant energy source for pelagic consumers (Canuel et al 1995;Jassby and Cloern 2000;Mueller-Solger et al 2002;Sobczak et al 2002Sobczak et al , 2005. Contributions of detrital material to pelagic consumers cannot be ruled out entirely, but for the purposes of our study phytoplankton is assigned as the basal source of food for pelagic food webs (i.e., consumers with depleted d 13 C signatures) based on its likely dominance in assimilation to upper trophic levels.…”
Section: Pelagic Food Websmentioning
confidence: 99%
See 2 more Smart Citations